Endometriosis: etiology, pathogenesis, diagnostics, modern aspects of treatment - N. V. Avramenko (Zaporozhye State Medical University, 2014)
Aim. To analyze the data of the current scientific literature on the etiology, pathogenesis, diagnosis, clinic and modern therapy of genital endometriosis, which is one of the most urgent problems of modern gynecological practice. Methods and results. The main role in the process of growth and development of endometriosis is currently attributed to changes in the function of the immune system, possibly genetically determined. Currently, it is proved that endometriosis develops immune processes against endometrial tissue. There is every reason to believe that endometrium in its unusual places can acquire antigenic properties that stimulates the body's immune system reaction. Hyperandrogenism, early menarche, heavy and prolonged menstruation, disorders of the outflow of menstrual blood, adverse environment, obesity, smoking, stress are considered as the risk factors for the development of endometriosis. Revised diagnosis is possible with laparoscopic visualization (ideally with confirming histological research). A presumptive diagnosis is based on typical clinical symptoms and signs. Laboratory methods of diagnosis: magnetic resonance imaging and ultrasound. The main methods of treatment of endometriosis are surgical, medication, combined. Conclusion. Endometriosis remains unresolved scientific and clinical problem characterized by the paradoxical aspects of the pathogenesis and clinical contrasts of course without found explanation yet.